The Maximal Oxygen Uptake and Lactate Threshold in Anaerobic Exercise: A Sub-Athletic Case Study - Kahmasi, Masoud (AlQalam Journal of Medical and Applied Sciences, 2025)
This case study was aimed to study and establish the physiological variables caused by incremental endurance training of one sub-athletic male subject. It was designed to test the lactate threshold [LT], economy and maximal oxygen uptake (VO2max.) throughout two distinct parts of incremental endurance exercise using cycling ergometer. in contrast to the main hypothesis that was suggesting; the lactate threshold, the point of sudden rise in blood (systemic) lactate during incremental endurance exercise will have a fatiguing effect on performance and would not allow researcher to ascertaining a true VO2 max. However, the main results indicated lactate threshold [LT] taken place at work rate of 120 (w) represents 66.5% of maximum subject’s heart rate, obviously it did not affect the true VO2 max. result. So, a combination of factors may explain the variation of lactate threshold. Or rather, that lactate does accumulate as [LT] has variable effects on the outcome of subject’s endurance performance. That is to say, the uneconomical increase in power expenditure (economy), in addition to other metabolic determinants. هذه دراسة حالة تهدف إلى دراسة وتحديد المتغيرات الفسيولوجية الناجمة عن تمرين التحميل المتزايد، لرياضي ثانوي متطوع موضوع البحث من الذكور. لقد تم تصميم التمرين لاختبار عتبة حمض اللاكتيك، وأقتصاد الطاقة، والحد الأقصى لإستهلاك الأكسجين (VO2max) خلال جزأين متميزين من تمرين التحميل المتزايد باستخدام دراجة مقياس الجهد. وعلى عكس الفرضية الرئيسية التي كانت تقترح أن عتبة اللاكتات هي نقطة الزيادة المفاجئة لحمض اللاكتيت في الدم (الدورة الدموية)، أثناء تمرين التحميل المتزايد سيكون لها تأثير التعب على الأداء، وبالتالي لن تسمح للباحث بالتأكد من قيمة VO2max الحقيقية. فمن ناحية أخرى، أشارت النتائج الرئيسية إلى أن عتبة اللاكتات التي حدثت عند معدل جهد قدره 120 (وات) تمثل 66.5% من الحد الأقصى لمعدل ضربات قلب الشخص موضوع البحث، ومن الواضح أنها لم تؤثر على الحد الأقصى الحقيقي لـ VO2. نتيجة لذلك فإن هناك مجموعة من العوامل قد تفسر اختلاف عتبة اللاكتات. أو بمعني آخر حدوث تراكم فعلي لللاكتات، لأن عتبة اللاكتيت لها تأثيرات متغايرة على نتائج أداء التحمل لدى الشخص المستهدف بالاختبار. ويمكن القول أن الزيادة غير الاقتصادية في استهلاك الطاقة، بالإضافة إلى المحددات الأيضية الأخرى لها دور في ذلك